Research typological properties of steels in hydrogen and vacuum at different temperature. - Арендар, Л. А.; Василів, Х. Б.; Коваль, Ю.М.; Гущак, Р.І. (Problems of Tribology, 2016)
The friction and wear of Armco iron and ferrite-pearlite steel types 20, 45, Y8 in a hydrogen atmosphere have been analyzed. Revealed brittle fracture of friction surface of Armco iron and steel 20 probably is a result of hydrogen absorption. It was shown that increasing the carbon concentration inside the steel causes the reduction of influence of hydrogen on its tri-bological properties. It can be explained by increasing the cohesive strength in metals and the ability of inter-phase ferrite-cementite surfaces to absorb hydrogen without creating additional resistance inside the lattice.